ДИПЛОМНЕ ПРОЄКТУВАННЯ ЯК ФОРМА ОЦІНЮВАННЯ ЯКОСТІ ПІДГОТОВКИ МАЙБУТНІХ ФАХІВЦІВ-ПРОГРАМІСТІВ (Innovative professional education, 2022)
Diploma design is considered as the final stage of training and the final form of monitoring the training of programmer specialists. During the diploma project, future programmers go through the entire life cycle of software development according to their qualifications. This ensures a deep and systematic examination of students' readiness for professional activity.
Keywords: diploma design, future programmer specialists, evaluation of the quality of training, professional pre-higher education